The Mind-Body Problem A Conversation with Janko Tipsarevic. - Burton, Howard (Ideas Roadshow Conversations Ser., 2020)
This book is based on an in-depth filmed conversation between Howard Burton and Janko Tipsarevic, who is a former professional tennis player with a career-high singles ranking of world no. 8 and founder and CEO of Tipsarevic Tennis Academy in Belgrade, Serbia. This conversation gives behind-the-scenes insights on what it takes to achieve excellence in professional sports, what mindset is needed to reach one's true potential and a penetrating and inspirational window into the psychology of professional tennis that resonates with all of us. This carefully-edited book includes an introduction, Gi.